2020
DOI: 10.1186/s12886-020-1330-8
|View full text |Cite
|
Sign up to set email alerts
|

Protection of retinal function and morphology in MNU-induced retinitis pigmentosa rats by ALDH2: an in-vivo study

Abstract: Background: Retinitis pigmentosa (RP) is a kind of inherited retinal degenerative diseases characterized by the progressive loss of photoreceptors. RP has been a conundrum without satisfactory countermeasures in clinic until now. Acetaldehyde dehydrogenase 2 (ALDH2), a major enzyme involved in aldehyde detoxification, has been demonstrated to be beneficial for a growing number of human diseases, such as cardiovascular dysfunction, diabetes mellitus and neurodegeneration. However, its protective effect against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…Furthermore, we confirmed the retinal protective ability of the RdECM using the Laser-CNV and the NMU-RD model due to their wide use as retinal degeneration models, including AMD and RP [ 55 , 56 , 57 , 58 ]. The RdECM-treated Laser-CNV mice showed similar wound recovery as the Avastin-treated mice, whereas the recovery was nearly unchanged in the collagen-treated mice.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, we confirmed the retinal protective ability of the RdECM using the Laser-CNV and the NMU-RD model due to their wide use as retinal degeneration models, including AMD and RP [ 55 , 56 , 57 , 58 ]. The RdECM-treated Laser-CNV mice showed similar wound recovery as the Avastin-treated mice, whereas the recovery was nearly unchanged in the collagen-treated mice.…”
Section: Discussionsupporting
confidence: 59%
“…27 Moreover, our recent study showed that ALDH2 could protect retinal function and morphology in rats with MNU-induced retinitis pigmentosa. 28 This evidence supports a beneficial role of ALDH2 in endothelial dysfunction, angiogenesis, neurodegeneration, and energy metabolism disturbance.…”
Section: Introductionsupporting
confidence: 52%
“…Moreover, ALDH2 has a certain protective effect in age-related disease, such as Alzheimer's Disease (AD), Parkinson's Disease (PD) and aged cardiopathy by decreasing free radicals damage [ 20 ]. Simultaneously, our previous animal experiments have also shown that ALDH2 could play a certain role in aged diabetic retinopathy [ 21 ] and retinitis pigmentosa (RP) [ 22 ]. Furthermore, our clinical retrospective data analysis showed that the aged with ALDH2*1* (G/G) genotype possessed a better retinal function and a thicker macula compared with ALDH2*2*2 (mutant heterozygous AA) while the young with different ALDH2 genotype, including ALDH2*1*1, ALDH2*1*2 (mutant heterozygous GA) and ALDH2*2*2, showed no significant difference ( Supplementary Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%